2011
DOI: 10.1007/s11010-011-1158-x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the SET protein in HEK293T cells and mild oxidative stress: cell survival or death signaling

Abstract: SET protein (I2PP2A) is an inhibitor of PP2A, which regulates the phosphorylated Akt (protein kinase B) levels. We assessed the effects of SET overexpression in HEK293T cells, both in the presence and the absence of mild oxidative stress induced by 50 μM tert-butyl hydroperoxide. Immunoblotting assays demonstrated that SET accumulated in HEK293T cells and increased the levels of phosphorylated Akt and PTEN; in addition, SET decreased glutathione antioxidant defense of cell and increased expression of genes enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
1
26
0
6
Order By: Relevance
“…Five-μm sections were stained with H&E for histological analysis. Three-μm sections were used for the immunohistochemical analysis of SET, Ki67, pan-CTKR, p62, pERK1/2, and p-p53 Ser15 proteins as previously described [5]. The following primary antibodies were used: Ki67 (ab15580; Abcam, Cambridge, England), p62/SQSTM1 (D-3: sc-28359; Santa Cruz Biotechnologies, Santa Cruz, CA, USA), pan-CTKR, SET, pERK1/2 and p-p53 Ser15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five-μm sections were stained with H&E for histological analysis. Three-μm sections were used for the immunohistochemical analysis of SET, Ki67, pan-CTKR, p62, pERK1/2, and p-p53 Ser15 proteins as previously described [5]. The following primary antibodies were used: Ki67 (ab15580; Abcam, Cambridge, England), p62/SQSTM1 (D-3: sc-28359; Santa Cruz Biotechnologies, Santa Cruz, CA, USA), pan-CTKR, SET, pERK1/2 and p-p53 Ser15 .…”
Section: Methodsmentioning
confidence: 99%
“…SET-mediated PP2A inhibition occurs via dephosphorylation of proteins, such as the extracellular signal-regulated kinase (ERK) [3] and protein kinase B (Akt) [4]. Recently, we demonstrated that SET accumulates in head and neck squamous cell carcinoma (HNSCC) and suggested a new role for SET as a sensor of oxidative stress, thereby promoting cell survival in association with increased phosphorylated Akt levels and an enhanced antioxidant defense [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Of importance, SET plays an oncogenic role modulating signaling pathways with high relevance in human cancer (11). For instance, it has been reported that SET activates the transcription factor AP-1, deregulates AKT signaling, inhibits the DNase activity of the tumor-suppressor NM23-H1, or negatively regulates p53 acetylation, thus repressing its activity (12)(13)(14)(15)(16). Moreover, SET is overexpressed in several neoplasms (17)(18)(19)(20)(21) and it has been proposed as a novel molecular target for anticancer therapy (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Almeida et al (16) assessed the effect of the overexpression of the SET protein, a histone acetylation modulator accumulated in head and neck squamous cell carcinoma, on the gene regulation and protein activity of aldehyde dehydrogenase 2 and glutathione S-transferase P1. Leopoldino et al (17) reported that accumulated set may act via the Akt̸PTEN pathway as a cell survival signal or as an oxidative stress sensor promoting cell death. The studies mentioned above indicated that set may be involved in the development of several malignant tumors.…”
Section: Genementioning
confidence: 99%